Analaysis of Educational Service Quality in the Faculty of Dentistry at Guilan University of Medical Sciences: A SERVQUAL Model Study - Padina Safa; Elham Jafari; Yasamin Babaee Hemmati; Mehran Falahchai (مجله دانشگاه علوم پزشکی گیلان, 2025)
Background: Evaluating educational service quality in dental schools is essential for academic improvement. Prior studies in Iran using the SERVQUAL model have consistently revealed gaps between students’ expectations and perceptions. Objective: To assess the quality of educational services at the Faculty of Dentistry, Guilan University of Medical Sciences, using the SERVQUAL model. Methods: This analytical cross-sectional study (2025) included 275 dental students (years 2–6) from the Rasht and Anzali campuses. A validated three-part SERVQUAL questionnaire was used (demographics, 27 perception items, and 27 expectation items across five dimensions). Validity and reliability were confirmed (CVR = 88%, CVI = 92%, Cronbach’s alpha > 0.78). Data were analyzed using SPSS-28 with t-tests, ANOVA, and Spearman correlation (α = 0.05). Results: The mean perceived quality was 2.71 ± 0.77, expected quality was 3.78 ± 0.94, and the total quality gap was -1.06 ± 1.17. The largest gap was observed in tangibles—likely due to inadequate infrastructure and outdated tools—while the smallest was in assurance, reflecting greater trust in staff competence. The quality gap was significantly lower in males than in females (p < 0.05). Additionally, as academic year increased, both perceived quality (r = 0.17, p = 0.005) and the quality gap (r = 0.12, p = 0.043) increased, possibly due to adjusted expectations or greater familiarity with the system. Conclusion: Educational service gaps were present across all dimensions. Institutions should prioritize upgrading resources, improving staff responsiveness, and conducting regular evaluations aligned with student feedback.